Optical observations of PSR J2021+3651 with the GTC. (November 2015) - Ryspaeva, E B; Kirichenko, A Yu; Shibanov, Yu A; Shternin, P S; Danilenko, A A; Zyuzin, D A; Durant, M; Kargaltsev, O Yu; Pavlov, G G; Cabrera-Lavers, A
Abstract: We analyzed first optical observations of 17 kyr-old PSR J2021+3651 and its pulsar wind nebula obtained with the 10.4-m Gran Telescopio Canarias (GTC) telescope in the Sloan r' band. In addition, we reanalyzed archival X-ray data obtained with Chandra . The pulsar and the nebula were not detected in the optical down to 27.20 and 24.85 magnitude 3σ limits, respectively. Using the optical and X-ray data we conclude that PSR J2021+3651, like the Vela pulsar, is a very inefficient nonthermal emitter in the optical and X-rays, while its gamma-ray efficiency is consistent with an average efficiency for all gamma-ray pulsars of similar ages.